EXPLORING LEGAL CHALLENGES IN MURABAHAH FINANCING: A JURIDICAL ANALYSIS OF WANPRESTASI DISPUTES IN CONSUMER LOANS - Fahri Gunawan Siagian; Reka Dewantara; Natsir Asnawi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study examines the wanprestasi dispute between PT. Bank Syariah Indonesia, Tbk and a debtor concerning a murabahah financing agreement. The Makassar Religious Court's decision upheld the enforceability of the murabahah contract and collateral under Hak Tanggungan but dismissed the debtor’s financial hardship claim due to the COVID-19 pandemic. The study highlights gaps in debtor protection and the need for clearer procedural guidelines on collateral execution, proposing improvements for aligning Sharia principles with practical dispute resolution in Indonesia’s growing sharia finance sector.